(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
According to literature, people with mental illnesses take various substances and chemicals to commit suicide. Such suicidal behavior is often observed among prisoners and military personnel.